Post-Stroke Survivors: The Relationship between Clinical Characteristics and the Levels of Depression - Bala Krishnian M; Leong, JWS; Lye, MS; Johar MJ; Ismail MS (Penerbit UKM, 2015)
Stroke is frequently associated with long-term disability. It is led to a high risk of physical and neuropsychological consequences. Residual disabilities among post-stroke survivors can lead them to depression. This study aimed to determine the relationship between clinical characteristics and the levels of depression among post-stroke survivors at a teaching hospital in Kuala Lumpur. This cross-sectional study recruited 195 post-stroke survivors who attended follow-up Rehabilitation Clinic of a teaching hospital over a study period of 4 months. Information collected included socio-demographic, clinical characteristics (post stroke duration, stroke types and stroke severities) and level of depression. Beck’s Depression Inventory (BDI) was used to assess the level of depression. The mean age of participants was 61 years (SD=13.86, range: 22-87 years), with 118 male and 81 female survivors having a median duration of post-stroke of 12 months (range: 1–79 months). This study showed post stroke survivors 116 (59.5 %) with depression. A Chi-square test for level of stroke severity was significantly associated with depression, χ2 (2, n=195) = 28.724, p< 0.001, phi = 0.384. The results of the present study showed that survivors with mild stroke have less depression (44.0 %) compared to moderate stroke (81.7 %) and severe stroke (87.5%).